Formal methods in macro-biology : First International Conference, FMMB 2014, Noumea, New Caledonia, September 22-24, 2014. Proceedings - Piazza, Carla; Fages, Francois (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the First International Conference on Formal Methods in Macro-Biology, FMMB 2014, held in Nouméa, New Caledonia, in September 2014. The 7 revised full and 3 short papers presented together with 7 invited presentations were carefully reviewed and selected from 17 submissions. The scientific program consists of papers on a wide variety of topics, including ecological systems, medical applications, logical frameworks, and discrete continuous and hybrid models for the analysis of biological systems at macroscopic levels.